2020
DOI: 10.31557/apjcp.2020.21.7.1969
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Gynecological Cancers: A Web-Based Study

Abstract: Introduction: Gynecological cancers are common in adult women. One of the most important goals in the management of these patients is to improve quality of life, along with survival as a traditional outcome. The aim of this study was to evaluate quality of life in gynecological cancers in Iran. Methods: This cross-sectional study was performed on a sample of patients with gynecological cancers including uterine, ovarian, cervical, and vulvovaginal attending a teaching h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Nowadays, there are few specific quality-of-life scales for patients with gynecological and breast cancer. Moreover, those that exist do not properly reflect some gynecological cancer-specific features, such as resilience, premature menopause or sexuality, that is why despite gynecological cancer modules are slowly emerging, specific scales for gynecological and breast cancer are required to develop and expand itselves [15,40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nowadays, there are few specific quality-of-life scales for patients with gynecological and breast cancer. Moreover, those that exist do not properly reflect some gynecological cancer-specific features, such as resilience, premature menopause or sexuality, that is why despite gynecological cancer modules are slowly emerging, specific scales for gynecological and breast cancer are required to develop and expand itselves [15,40].…”
Section: Discussionmentioning
confidence: 99%
“…In short, many women worsen their quality of life because of cancer treatment [15,35]. Due to the common peculiarities to most gynecological and breast cancers, which have to do with aesthetic sequels secondary to mutilating surgeries, the possibility of suffering an induced and early menopause and dissatisfaction in sexual intercourse, makes it necessary to validate specific health related quality of life and resilience scales for this concrete group of patients [3,4,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that patients with cancer face numerous challenges in their marital life such as divorce, and in fact their illness has a more negative impact on their marital life than they expected (32,33). On the other hand, it has been found that women are more likely to get divorced when diagnosed with cancer than men (34).…”
Section: Discussionmentioning
confidence: 99%